Incidence of new carotid plaques in rheumatoid arthritis patients: 6-Year prospective results of the TOMORROW study. Issue 3 (2nd June 2022) - Anno, Shohei; Okano, Tadashi; Mamoto, Kenji; Sugioka, Yuko; Tada, Masahiro; Inui, Kentaro; Koike, Tatsuya; Nakamura, Hiroaki
ABSTRACT: Objectives: The purpose of this study was to evaluate the new incidence of carotid plaques in rheumatoid arthritis (RA) patients over a 6-year prospective follow-up and to assess the risk factors. Methods: This is a 10-year prospective cohort study that included 208 RA patients and 205 age- and gender-matched controls. Ultrasound assessment of the bilateral carotid arteries was performed in 2011 and 2017. Results: There were no differences in the incidence of new carotid atherosclerotic plaques over 6 years between the two groups (35.5% vs. 37.0%, respectively; p  = .936). The mean Disease Activity Score 28-C-reactive protein over 6 years in RA patients was 2.73 ± 0.95. Multiple logistic regression analysis showed that RA was not a risk factor for new carotid atherosclerotic plaques (odds ratios, 0.708; 95% confidence interval, 0.348–1.440; p  = .340). An average glucocorticoid dose of >1.8 mg/day over 6 years was a risk factor for new carotid atherosclerotic plaques (odds ratios, 8.54; 95% confidence interval, 1.641–44.455; p  = .011). Conclusions: Incidence of new carotid atherosclerotic plaques was similar between well-controlled disease activity RA patients and control subjects. A mean glucocorticoid dose of >1.8 mg/day over 6 years was a risk factor for new carotid atherosclerotic plaques.